Effectiveness of different preventive agents on initial occlusal and proximal caries lesions: A follow-up study - Said Karabekiroğlu; Fatma Betül Kahraman; Nimet Ünlü (Elsevier, 2018)
Background/purpose: Monitoring the effects of different caries-preventive agents on initial caries lesions in orthodontic patients is important. Therefore, the purpose of this study is to investigate the efficacy of different preventive methods in preventing occlusal and proximal incipient lesions (ILs) during fixed orthodontic treatment. Materials and methods: Forty-eight subjects at the beginning of fixed orthodontic treatment were included. All subjects were well educated and motivated to use the fluoride toothpaste (Colgate Total, 1450 ppm F) three times a day during the study period. Four different groups were created with a split-mouth design: placebo, fluoride gel, fluoride varnish, and chlorhexidine varnish. The occlusal surfaces of the second molar teeth were assessed with DIAGNOdent pen (DD) during the first 12 months (6th and 12th), and the proximal surfaces of each quadrant were monitored using bitewing radiographs until the 24th month (baseline and 24th month). Results: The mean DD values increased in each group during the first 6 months compared to the baseline, but a significant increment was only obtained in the control and fluoride gel groups (p < 0.05). Fluoride and chlorhexidine varnish had significantly more preventive effects than the control and the fluoride gel for occlusal surfaces at the 6th and 12th month and for intact proximal surfaces at the 24th month, but no significant differences were found between the two varnish groups (p > 0.05). No significant differences were found between the four methods in terms of caries progression for proximal ILs after 24 months. Conclusion: Effective toothbrushing with 1450 ppm fluoridated toothpaste and topical fluoride gel application seems to be inadequate for prevention of new proximal ILs during fixed orthodontic treatment. Fluoride and chlorhexidine varnish showed more protection in relation to occlusal surfaces.